Case Study of Twitter Trending Topic: Analysis of Using Random 4 Digits to Raise the Hashtags on Twitter - Nadhiar Ridho Wahyu Pradana (Budapest International Research and Critics University, 2021)
In 2021 Twitter is the fifth most popular social media in Indonesia. One of the uniqueness of twitter compared to other social media is the hashtag (# symbol) which is placed at the beginning of words or phrases typed on social networks. Hashtags will make it easier for Twitter users to find specific information. With this hashtag feature, many Twitter users are competing to make a hashtag trending or even competing to make their hashtag trending. There is a unique method used to increase a hashtag by using a 4 digit random hashtag at the end of the tweet. This phenomenon is often found in trending hashtags with the caliphate theme. Based on the results of the analysis that has been carried out related to the use of 4-digit random hashtags, it shows that the 4-digit hashtag code is one of the tools to generate tweets that are as unique as possible, both in terms of the account using, content, activity type, activity target, and media to raise hashtags on Twitter. This 4-digit hashtag code is suspected to be the activity of an account along with the content being played. Accounts that use the same code more than once are unlikely to have different content. Likewise, when the same account plays different content, it must be accompanied by a different code. This indicates the relationship between the account and the 4-digit hashtag, to the content being played. Recently, hashtags around the Caliphate that use random hashtags have switched to using 5-digit random hashtags. The intent and purpose of its use is still the same as using a 4-digit random hashtag.